Phase II study of ipilimumab in adolescents with unresectable stage III or IV malignant melanoma. (November 2017) - Geoerger, Birgit; Bergeron, Christophe; Gore, Lia; Sender, Leonard; Dunkel, Ira J.; Herzog, Cynthia; Brochez, Lieve; Cruz, Ofelia; Nysom, Karsten; Berghorn, Elmer; Simsek, Burcin; Shen, Jun; et al.
Abstract: Background: Ipilimumab is approved for the treatment of advanced melanoma in adults; however, little information on the efficacy and safety of ipilimumab in younger patients is available. Methods: Patients aged 12 to <18 years with previously treated or untreated, unresectable stage III or IV malignant melanoma received ipilimumab 3 or 10 mg/kg every 3 weeks. Primary end-points were 1-year overall survival and safety. Results: Over a period of 3.5 years, 12 patients received ipilimumab at either 3 mg/kg (n = 4) or 10 mg/kg (n = 8). The median number of ipilimumab doses was four for 3 mg/kg and three for 10 mg/kg. At 1 year, three of four patients on 3 mg/kg and five of eight patients on 10 mg/kg were alive. Two patients on 10 mg/kg had partial response, and one on 3 mg/kg had stable disease. One patient had durable partial response at 3 years without further treatment, at time of this report. There was one grade 3/4 immune-mediated adverse reaction with 3 mg/kg and five with 10 mg/kg. There were no treatment-related deaths. The study was stopped due to slow accrual. Conclusions: At >1 year follow-up, ipilimumab demonstrated activity in melanoma patients aged 12 to <18 years, with a similar safety profile as that seen in adults. Our trial highlights the difficulties of enrolling younger patients with rare diseases in clinical trials for treatments that are approved in adults, suggesting adolescents with cancer types occurring predominantly in adults should be considered for inclusion in adult trials of promising new drugs. Clinical trial registration:NCT01696045 . Highlights: Phase II study of ipilimumab in adolescents with advanced melanoma. At 1 year, 3 of 4 patients on 3 mg/kg and 5 of 8 patients on 10 mg/kg were alive. Two patients on 10 mg/kg had partial response and 1 on 3 mg/kg had stable disease. The safety profile was consistent with that observed in the adult population. The study was stopped due to slow accrual of patients.